THE JIHAD MOVEMENT: A CRITICAL ANALYSIS OF THE THOUGHT OF IBNU TAIMIYAH, SAYYID QUTB, AND QURAIH SYIHAB - Ulul Albab; Sopiah Sopiah; Makmun Makmun; Nasikhin Nasikhin; Musthofa Musthofa; Abdullah Penaemale (STIT Sunan Giri Bima, 2023)
This study aims to execute the meaning of jihad from the perspective of Ibnu Taimiyyah, Sayyid Quttub, and Quraih Syihab. By using the literature study method, this study shows that; 1) In the perspective of Ibn Taimiyyah, jihad is defined as a war that is not like today's terrorists. Even in war, one must follow predetermined ethics, namely: not to attack first, not to kill people who have nothing to do with war, and killing is only permitted if there is good for it. Meanwhile, according to Sayyid Quttub jihad is defined as a movement by preaching. Quraish Syihab sees that the most important jihad is against satan and lust. According to him satan is the most dangerous enemy for Muslims. Thus, fighting it is a must for every individual. In addition, even though he also interprets jihad as war. However, the war in question is defensive in nature, namely an effort to carry out self-defense if the enemy first wages war. 2) Both Ibnu Taimiyyah, Sayyid Quttub, and Quraih Syihab, all three agree that the context of jihad is divided into two definitions. First, the context of jihad is defined as war, and the context of jihad is defined as sincerity in achieving something whose goal is to get closer to Allah, and distance oneself from anything that is forbidden by Him. In the perspective of the arguments in the Qur'an and Hadith, the context of jihad is interpreted in various ways. Jihad can be interpreted as serving parents, helping widows or people in need, and war. However, the war that is carried out also needs to follow the rules applied in Islamic teachings. Even Rasulullah is a spreader of peace. So he prefers the path of peace rather than war. This research contributes to supporting the concept of religious moderation, emphasizing that jihad does not always have to be done with war so that it clears people's minds that terrorism is not part of Islamic jihad.